Level Of Digital Literacy Understanding In Rt 15, Sawah Lebar Baru Urban Village, Bengkulu City - Muhammad Heri Saputra; Diva Parera; Putri Maretta Gultom; Retni Ardiana; Sella Syaputri; Ahmad Asyhari (Universitas Dehasen Bengkulu, 2026)
This study investigates the digital literacy proficiency among residents in RT 15, Sawah Lebar Baru Urban Village, Bengkulu City. Given how pervasive digital technology has become, it is crucial to assess the community's capabilities in safely accessing, managing, integrating, evaluating, and creating information. We utilized a descriptive quantitative approach, collecting data through a survey administered to the household heads in the area. The results indicate that most residents fall within a moderate level of digital literacy understanding. While basic digital proficiencies such as utilizing social media for communication and routine information retrieval are evident, there is a clear shortcoming in higher-order skills. This gap is most notable concerning digital security awareness and the capacity for critical evaluation of online content. The research recommends focused educational programs designed to bolster advanced digital competencies, thereby enabling the community to more effectively and securely capitalize on the opportunities presented by the digital landscape for personal and economic growth.